Effects of Financial development and institutions on firm in Malaysia - Lee, Huay Huay; Law, Siong Hook; Lee, Chin; W. Azman-Saini, W. N. (Universiti Malaysia Sarawak, 2022)
This study is motivated to examine if firm growth is dependent on access to external finance but subject to the macroeconomic environment. Using firm-level data from firms listed in Bursa Malaysia for the 2006-2014 period, the study applies dynamic panel system generalized method of moments (GMM) estimation (Blundell & Bond, 1998) to estimate how a country’s embedded financial development and institutional quality impacts the linkage of firms’ external financial dependence and growth opportunities to firm growth. A dynamic system GMM approach is employed to address the endogeneity and serial correlation concern. Firms that have greater growth opportunities actually grow faster with better financial development with embedded good institutions in the case of Malaysia. So findings concluded that firms experience higher growth through better allocation of finance since they have good potential to grow. This has shed important light on policymakers in formulating the design of many financial development policies across a wide set of countries aimed at fostering financial markets and the banking services sector to provide the vital sources of external financing needed by corporations in financing their investments. A well-functioning financial system is a necessary condition for promoting firm growth.